2017
DOI: 10.1039/c6cs00921b
|View full text |Cite
|
Sign up to set email alerts
|

Recent advances in nanomaterials for water protection and monitoring

Abstract: The efficient handling of wastewater pollutants is a must, since they are continuously defiling limited fresh water resources, seriously affecting the terrestrial, aquatic, and aerial flora and fauna. Our vision is to undertake an exhaustive examination of current research trends with a focus on nanomaterials (NMs) to considerably improve the performance of classical wastewater treatment technologies, e.g. adsorption, catalysis, separation, and disinfection. Additionally, NM-based sensor technologies are consi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
184
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 485 publications
(186 citation statements)
references
References 730 publications
0
184
0
2
Order By: Relevance
“…The difference between the two BET values was approximately 5.5 %, which can be attributed to nine years of storage that may have resulted in slight structural degradation, or a measurement error (human or instrumental). The average Barrett‐Joyner‐Halenda (BJH) specific pore volume of m‐Ag−SiO 2 was also higher (0.8 cm 3 g −1 ) than those reported in the literature for other (0.1–0.7 cm 3 g −1 ) SiO 2 −Ag products . The adsorbed volumes determined from the two isotherms lay between 250 and 500 cm 3 g −1 , which clearly demonstrated the higher specific surface area of the m‐Ag−SiO 2 sample compared to that of typical m‐SiO 2 prepared by the original TLCT method; the specific pore volume of a typical m‐SiO 2 sample is usually in the 200–350 cm 3 g −1 range.…”
Section: Resultsmentioning
confidence: 62%
See 2 more Smart Citations
“…The difference between the two BET values was approximately 5.5 %, which can be attributed to nine years of storage that may have resulted in slight structural degradation, or a measurement error (human or instrumental). The average Barrett‐Joyner‐Halenda (BJH) specific pore volume of m‐Ag−SiO 2 was also higher (0.8 cm 3 g −1 ) than those reported in the literature for other (0.1–0.7 cm 3 g −1 ) SiO 2 −Ag products . The adsorbed volumes determined from the two isotherms lay between 250 and 500 cm 3 g −1 , which clearly demonstrated the higher specific surface area of the m‐Ag−SiO 2 sample compared to that of typical m‐SiO 2 prepared by the original TLCT method; the specific pore volume of a typical m‐SiO 2 sample is usually in the 200–350 cm 3 g −1 range.…”
Section: Resultsmentioning
confidence: 62%
“…Moreover, the pore distribution was unchanged after 9 y, as evidenced by Figure , insets (c) and (d), indicating that m‐Ag−SiO 2 has an ultrastable structure. The BET specific surface areas of the material determined in 2008 and after 9 y of storage were 1835 and 1735 m 2 g −1 , respectively, with an average value of 1785 m 2 g −1 , which is very high compared to that of mesoporous materials obtained by the original TLCT method, and superior to that of other mesoporous SiO 2 −Ag products reported in the literature . The difference between the two BET values was approximately 5.5 %, which can be attributed to nine years of storage that may have resulted in slight structural degradation, or a measurement error (human or instrumental).…”
Section: Resultsmentioning
confidence: 67%
See 1 more Smart Citation
“…[105][106][107] Thinfilm nanofiber membranes have been developed for various water treatment processes. [105][106][107] Thinfilm nanofiber membranes have been developed for various water treatment processes.…”
Section: Water Treatmentmentioning
confidence: 99%
“…Reports have also shown that attachment of multiple, hydroxyl, carboxylic acid, and glycolic oxide on C 60 instigates photodynamic cycotoxicitly against pathogenic microorganisms including multi-antibiotic-resistant bacteria (Yamakoshi et al, 2003;Thota et al, 2012). The biocidal activity of C 60 is been mostly attributed to it's ability to generated reactive oxygen species (ROS) such as singlet oxygen and superoxide through photosensitization when it interacts with organic solvents (Das et al, 2017;Arbogast, Foote, & Kao, 1992;Barkry et al, 2007).…”
Section: A Antioxidant/biophamaleuticalsmentioning
confidence: 99%